Effects of traditional Thai boxing exercise program on physical performance in elderly Thai subjects: A pilot study. - Srisamai , T.; Nakmareong , S.; Yonglitthipagon, P.; Siritaratiwat, W.; Auvichayapat , P.; Sawanyawisuth , K.; Janyacharoen, T. (Chulalongkorn Medical Journal, 2023)
Background : The elderly take more risk of both chronic and acute illness, which in turn lead to loss of abilities in conducting their daily life. Exercise has become an important element that can improve their physical performance. Previous studies have found that the traditional exercise could improve physical performance of the elderly. Traditional Thai boxing exercise is a type of exercise that is traditional and based on Thais’ way of living. The pattern of movement combined arms and legs, so similar to the exercise pattern. Therefore, the researcher believed the traditional Thai boxing exercise should be an appropriate type of exercise for the elderly that could be performed sustainably and continuously. Objective : This research was to study the effect of the traditional Thai boxing exercise on physical performance in the elderly. Methods : This is an experimental study on 30 elderly. All participants were interviewed for their baseline information and examined according to the inclusion criteria before signing their informed consent forms. Then they underwent the six-minute walk test (6MWT), five times sit to stand test (FTSS), timed up and go test (TUGT) and quality of life test according to the World Health Organization quality of life – brief Thai version (WHOQOL-BREF THAI) prior to 8 weeks after intervention. The experimental group practiced traditional Thai boxing exercise for a period of 40 minutes per session, 3 times per week for 8 weeks. The control group received instructions on their general exercise and correct daily practices so that they would apply in their daily life. Result : The experimental group had a statistically significant difference in exercise capacity, lower leg strength, balance and quality of life. In contrast, the control group had no statistically significant difference in 6MWT and FTSS whereas TUGT and WHOQOL-BREF THAI had a statistically significant difference. The comparison between groups showed statistically significant difference in the 6MWT, FTSS, TUGT and WHOQOL-BREF THAI. Conclusion : The traditional Thai boxing exercise can improve physical performance in the elderly.